The impact of music therapy on anxiety and pregnancy rate among infertile women undergoing assisted reproductive technologies: a systematic review and meta-analysis - Marwa Yahia Mahmoud; Kareem Labib; Sileem Ahmed Sileem; Faisal Ali Mustafa; Wael M. Hamed; Ahmed Abd Elhamid; Doaa M. Saleh; Ahmed Alanwar; Amr Ahmed Mahmoud Riad; Ahmed Mohamed Abdelhakim; Ahmed M. Abbas; Heba M. Mohammed (Taylor & Francis Group, 2022)
Objective: We aimed to perform a systematic review and meta-analysis to evaluate the effect of music therapy on anxiety and pregnancy rates among infertile women undergoing to perform assisted reproductive technologies (ART). Methods: Cochrane Library, PubMed, ISI web of science, and Scopus were searched from inception to May 2021. We included randomized controlled trials (RCTs) that compared music therapy (intervention group) to no music intervention (control group). Our primary outcomes were anxiety score using the State-Trait Anxiety Inventory (STAI) tool and pain score utilizing the Visual Analog Scale (VAS). Our secondary outcomes were the overall satisfaction score and clinical pregnancy rate. We extracted the available data from included studies and pooled them in a meta-analysis model using RevMan software. The overall quality of evidence was assessed through GRADEpro GDT software. Results: Seven RCTs with a total number of 793 patients were included in our study. Music therapy significantly reduced the anxiety score compared to control group (MD= −3.09, 95% CI [−5.57, −0.61], p = 0.01). Moreover, pain score was significantly improved after music treatment (MD= −2.93, 95% CI [−3.86, −2.00], p > 0.001). A significant improvement in the overall satisfaction score was found among music therapy group (MD= 1.51, 95% CI [0.40, 2.61], p = 0.008). Although more women in music therapy group experienced an increase in the clinical pregnancy rate in comparison with control group, the result was not statistically significant (RR= 1.08, 95% CI [0.94, 1.26], p = 0.28). The GRADEpro GDT tool showed a moderate quality of evidence for the evaluated outcomes. Conclusions: There is evidence of moderate quality that music therapy improves anxiety, pain, and satisfaction scores among infertile women undergoing ART. Moreover, it increases the clinical pregnancy rate but without statistical significance. More trials with a larger sample size are needed to investigate the influence of music therapy on the clinical outcomes of ART.